Ectogenesis : artificial womb technology and the future of human reproduction - Gelfand, Scott; Shook, John R. (Value inquiry book series, 2006)
This book raises many moral, legal, social, and political, questions related to possible development, in the near future, of an artificial womb for human use. Is ectogenesis ever morally permissible? If so, under what circumstances? Will ectogenesis enhance or diminish women's reproductive rights and/or their economic opportunities? These are some of the difficult and crucial questions this anthology addresses and attempts to answer.